Effects of beta-aminopropionitrile fumarate and exercise on equine tendon healing: Gross and histological aspects - Alves, Ana Liz Garcia [UNESP]; Rodrigues, MAM; Aguiar, AJA; Thomassian, A.; Nicoletti, JLM; Hussni, Carlos Alberto [UNESP]; Borges, Alexandre Secorun [UNESP] (William E Jones Dvm, 2001)
In the present study, the effects of intralesional injections of beta-aminopropionitrile fumarate (BAPN-F) was assessed in equine experimental tendinitis. BAPN-F is a lathyrogen which inhibits crosslinking of collagen, permitting more time for parallel reorientation of the repair tissue. Sixteen two-year-old Arabian horses without health problems were used in this experiment. The animals were divided into two groups: group one was left in box rest, and group two was submitted to controlled exercise during the experiment. Tendinitis was induced with collagenase in the superficial flexor tendon of both forelimbs. Twenty days after the induction of tendinitis, intralesional treatment with BAPN-F was performed and the contralateral limbs received saline. A biopsy was obtained and gross and histopathological analysis was performed on the 150th day of the experiment. The collagen fibrillar alignment pattern in the heating area was better in the BAPN-F group submitted to controlled exercise than in the other group, as observed by sonographic and histopathologic examination. The present results indicate that BAPN-F in combination with controlled loading improved sear remodeling and tendon wound collagen maturation.